Fluorine-18 fluorocholine PET-CT localizes hyperparathyroidism in patients with inconclusive conventional imaging: a multicenter study from the Netherlands. Issue 12 (December 2016) - Kluijfhout, Wouter P.; Vorselaars, Wessel M.C.M.; van den Berk, Sandra A.M.; Vriens, Menno R.; Borel Rinkes, Inne H.M.; Valk, Gerlof D.; van Dalen, Thijs; de Klerk, John M.H.; de Keizer, Bart
Abstract : Background: Several reports have shown good performance of fluorine-18 fluorocholine ( 18 F-FCH) PET-computed tomography (CT) for parathyroid localization, although overall evidence remains scarce. We collected data from three institutions in the Netherlands and investigated the performance of 18 F-FCH PET-CT as a second-line imaging modality. Materials and methods: We performed a retrospective review of all patients at least 18 years who underwent 18 F-FCH PET-CT for biochemically proven hyperparathyroidism (HPT) and inconclusive ultrasound and sestamibi scintigraphy. Acquisition of PET images was performed 30 min after the administration of 2 MBq/kg 18 F-FCH, together with a low-dose CT. Results: PET-CT scans were performed in 33 (75%) women and 11 (25%) men with a mean age of 58.9 (range 31–80 years). Three patients had multiple endocrine neoplasia type 1, one patient had tertiary HPT because of Alport syndrome and the remaining patients had sporadic primary HPT. 18 F-FCH PET-CT was positive in 34/44 (77.3%) cases. Of the 35 abnormal glands resected in 33 patients, 18 F-FCH PET-CT could successfully localize 33/35 (94.3%), with only one false-positive result [positive predictive value (PPV)=97.1%]. Comparison of the 10 patients with negative PET-CT with the 34 patients with positive PET-CT showed no significant differences in age, sex, ratio of preoperative calcium, use of cinacalcet, history of neck surgery, and concomitant multinodular goiter. Conclusion: Our study shows excellent performance of 18 F-FCH PET-CT in patients with HPT and inconclusive conventional imaging. Because of its favorable characteristics with high performance, prospective studies should be initiated to determine whether this new technique may replace conventional sestamibi scintigraphy as a first-line imaging modality. Abstract : Supplemental Digital Content is available in the text.